Pengenalan Kuliner Tradisional Es Pisang Ijo sebagai Jembatan Budaya Organisasi Aisyiyah Ranting Suterejo Surabaya - Riskianti Riskianti; Ulfa Al Wafiah; Wahyuni Suryaningtiyas; Linda Mayasari; Badruli Martati (Pusat Riset dan Inovasi Nasional, 2025)
This community engagement activity aims to introduce and promote Es Pisang Ijo, a traditional culinary delight from Makassar, to the mothers of Aisyiyah Ranting Suterejo in Surabaya. The program was implemented through the National KKN-Dik collaboration between Universitas Muhammadiyah Makassar and Universitas Muhammadiyah Surabaya. The method applied was a field study involving several stages—explanation, demonstration, and direct hands-on practice. The activity received a highly positive response, as participants were actively involved in every phase, showing enthusiasm and curiosity. The outcomes of this activity include improved culinary skills, strengthened cultural awareness, and the creation of new opportunities for micro-enterprise development rooted in traditional cuisine. Additionally, this program enhanced cross-cultural communication and strengthened social solidarity among Aisyiyah members. Es Pisang Ijo thus represents not only a dessert but also a symbol of togetherness, women’s empowerment, and cultural preservation. This initiative reaffirms Aisyiyah’s role as an empowered women’s community that contributes to economic independence and cultural resilience through traditional culinary innovation as a medium of empowerment and community development.